Evaluasi Kemampuan Alat Gali Muat Excavator SANY SY500H Untuk Mencapai Target Produksi Pengupasan Overburden 184.571 BCM/Bulan Menggunakan Metode Overall Equipment Effectiveness Di Pit A PT. Mandiangin Batubara Kab.Musi Banyuasin Provinsi Sumatera Selatan - Muhammad Luthfi; Mulya Gusman (Journals Mining Engineering : Bina Tambang, 2023)
PT Mandiangin Batubara targets overburden stripping production in June 2022 of 184,571 bcm in the highwall bottom area of pit A, while for the realization of the ability of the SANY SY500H Excavator, the resulting production is only 121,347 bcm / month. The non-achievement is also due to the low effective working time which is only 367.76 hours / month and 358.74 hours / month from the available time of 641 hours / month.Efforts that can be made to analyze based on the problem are in the form of analysis using the overall equipment effectiveness method and determining losses based on the six big losses of equipment. Then proceed with grouping the root cause of the problem of non-achievement of production, namely with the Fishbone diagram. From the results of the analysis based on the six big losses, it was obtained that the highest losses occurred in Equipment Failure Losses of 42.62% and 44.03% respectively. After repairing the loss time, the total production of Overburden stripping was 221,925 bcm which means that the results of these improvements can exceed the production target by increasing the OEE value of the digging and loading equipment by 48% and 54% respectively.